2008
DOI: 10.1111/j.1095-8312.2008.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Using image analysis on the ventral colour pattern in Salamandrina perspicillata (Amphibia: Salamandridae) to discriminate among populations

Abstract: The ventral colour pattern in Salamandrina perspicillata is characteristic of each individual and remains invariant throughout the salamanders' life. The present study aimed to determine, using statistical methods applied to quantitative image analysis, whether the coloration pattern is population-specific. The images of ventral colour pattern of 180 salamanders belonging to five populations were analysed. The images were previously warped by geometric morphometry. To our knowledge, this is the first study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…In lizards, the general pattern of skull allometry, both in an ontogenetic (MonTEIro & ABE, 1997;kALIonTzopoULoU et al, 2008;rAIA et al, 2010) and static coSTAnTInI et al, 2010;LJUBISAvLJEvIć et al, 2011;zUFFI et al, 2011) context, includes a relative shortening of the anterior area and an enlargement of the posterior region. Interestingly, some studies have reported a lack of an allometric relationship between head shape and size in some lizard species (vIDAL et al, 2005(vIDAL et al, , 2006; however, these results should be considered with caution, since in the above studies, allometry was investigated by bivariate regression of the first principal component of shape variation on centroid size, thus potentially providing an incomplete view of allometric patterns.…”
Section: Allometric Patterns: Shape Change Due To Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In lizards, the general pattern of skull allometry, both in an ontogenetic (MonTEIro & ABE, 1997;kALIonTzopoULoU et al, 2008;rAIA et al, 2010) and static coSTAnTInI et al, 2010;LJUBISAvLJEvIć et al, 2011;zUFFI et al, 2011) context, includes a relative shortening of the anterior area and an enlargement of the posterior region. Interestingly, some studies have reported a lack of an allometric relationship between head shape and size in some lizard species (vIDAL et al, 2005(vIDAL et al, , 2006; however, these results should be considered with caution, since in the above studies, allometry was investigated by bivariate regression of the first principal component of shape variation on centroid size, thus potentially providing an incomplete view of allometric patterns.…”
Section: Allometric Patterns: Shape Change Due To Sizementioning
confidence: 99%
“…A very promising methodology for the field of biomechanics was put forward by pIErcE et al (2008) and STAyTon (2009), who joined shape theory and finite element models to study the mechanical properties of the crocodilian skull and three-dimensional turtle shell shape correspondingly. Finally, although not directly linked to the study of shape variation, it is worth mentioning the use of GM tools as a means of standardising specimen position for studying colour patterns in salamanders (ASHLock et al, 2003;coSTA et al, 2009). …”
Section: Amphibians and Reptiles As Models For The Development Of Newmentioning
confidence: 99%
“…The substantial improvement of all goodness-offit indicators is probably the most visible benefit. Moreover, other benefits of the PLS regression technique are not merely the increase of a coef- ficient, but the capacity of detecting significant variables otherwise missed with ordinary regression techniques (Costa et al 2009). This is the advantage of latent vectors, which are capable of integrating the effect of more independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…This technique originated within the field of economics (Wold 1966) but became popular first in computational chemistry (Geladi and Kowalski 1986) and then in sensory evaluation (Martens and Naes 1989). Today PLS regression is becoming a tool of choice in the social sciences, as a multivariate technique for non-experimental and experimental data alike (Mcintosh et al 1996, Costa et al 2010, Capoccioni et al 2011. PLS regression was first presented as an algorithm akin to the power method used for computing eigenvectors and was rapidly interpreted in a statistical frame-work (Frank and Friedman 1993, Helland 1990, Hoskuldsson 1988, Abdi 2003.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a proper superimposition between color (starchiodine test image, SITi) and NIR images (NIRi), each SITi was warped (rotated, scaled and translated) with the same angle of each NIRi, having the two images the same reference point (a needle). After the warping procedure, the two images had the same angle, size and resolution (Costa et al 2008c). A bounding box of both SITi and NIRi was extracted; the background and internal carpellar spaces were consequently eliminated from the analysis.…”
Section: Color Image Segmentationmentioning
confidence: 99%